Scope and Career Opportunities of Web Technology Subject of BICTE Program - Choudhary, Rajesh K. (Triyuga Academic Journal, 2024)
Web technology refers to the various tools and techniques used in the process of communication between different types of devices used on the Internet. This research paper explores the importance of web technology and opportunities related to web technology in Information Communication Technology and Education (BICTE) program. This article provides Importance of subject matter related to web technology to the students completing this degree and explores the career prospects after completing this degree. This article also highlights the evolving state of web technologies and their relevance in shaping the modern information technology industry.